Numerical simulation of the transient temperature distribution inside a close-packed array of cylindrical tubes during heating and cooling under high vacuum - Pissanetzky, Sergio (North-Holland Publishing Company, 1980)
Fil: Pissanetzky, Sergio Comisión Nacional de Energía Atómica; Argentina